Sociocultural approach to the feminine genital mutilation - Yusimy Luján Risco; Pablo Ricardo Betancourt Álvarez; Ángela Fajo Betancourt (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
The feminine genital mutilation is registered among the harmful traditional practices recognized as form of violence against the women and the girls. Complex topic, delicate and politicized, difficult to understand through normative definitions, classifications and geographical delimitation. Its ignorance, on the part of the professionals of the health, can contribute to an inadequate handling of the patients, as part of their integral attention. The work takes as an objective to argue on sociocultural aspects of the Feminine Genital Mutilation, essential for its integral handling for the health professional. The approach, called "five P" is recommended: predominance, prevention, protection, pursuit and provision of services. Moreover, the reproach attitudes must be avoided or victimization towards the patient, expression of a euro-central and paternalistic look towards the different, unexpected or unknown; as well as not to promote the medicalization of the practice.